Analisis pengaruh rasio kinerja keuangan terhadap profitabilitas bank pembiayaan rakyat syariah di indonesia - Azmy, Ahmad (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
This research analyzes about the influence of financial performance ratio to profitability of Rural Bank of Sharia in Indonesia. Financial performance ratio variables are proxied by the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Income Operating Expenses (BOPO). Profitability ratio is proxied with Return on Assets (ROA) and Return on Equity). The method used is Lin-Log Logarithm Transformation on Multiple Regression model. The results explain that the Capital Adequacy Ratio (CAR) ratio has no effect and the direction of negative moving relation to ROA and ROE. Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR) ratios have a negative moving influence and direction towards ROA and ROE. Operating Expense and Operating Revenue Ratios have a significant influence. Direction of negative moving relation to Return on Assets (ROA) and positive to Return on Equity (ROE). This study found that the profitability of Sharia Rural Banks in Indonesia (BPRS) is influenced by the level of problem financing, proper allocation of financing, and the balance of operational efficiency.